Results of experimental and computational studies for steam turbine exhaust hoods applying a wide-mode deflector - Lapuzin, Alexander; Malymon, Ivan; Subotovich, Valery (Institutul Internațional de Management Imi-Nova, 2023)
Research of exhaust hoods operation combined with the turbines’ last stages at reduced volume flow rates is of high scientific importance. With a decrease of load in the diffusers, flow passage the bushing circulation zone of the separated flow increases, which affects the efficiency of the turbine outlet part. During the first phase, an aerodynamic experiment was executed, that studied an outlet hood model of the powerful steam turbine, as well as the turbine’s last stage. Based on the results of the experiment carried out in wide operating modes range of the turbine last stage, it was determined that the installation of a wide-mode deflector at the inlet to the diffuser allows to reduce the separated circulation flows and the nonuniform flow in the outlet hood, as well as to reduce the total loss coefficient. During the second phase, computational studies were performed that used CFD four design forms of an axial-radial diffuser, distinguished by presence or absence of deflectors. It was determined that in the studied range of operating modes, all design forms of the diffuser with a wide-mode deflector have a positive effect on the flow – the total loss coefficient decreases and the efficiency of the turbine outlet part increases respectively, while the dimensions of the bushing circulation zone significantly decrease. The research results can be used both in the development of new exhaust hoods designs and in the modernization of the operated turbines flow path.
Keywords: circulation zone; diffuser; loss coefficient; operating mode